ON THE POETIC ART AND ELEMENTS OF NICKNAMES (Scientific journal of the Fergana State University, 2023)
The article provides an analysis of poetic arts such as tanosib, ittifoq, iyhom, tajnis, which are formed on the basis of nicknames, and poetic elements and methodological tools such as radif, nido.